Resource Partitioning Between Phytoplankton and Bacteria in the Coastal Baltic Sea - Sörenson, Eva; Farnelid, Hanna; Lindehoff, Elin; Legrand, Catherine (Frontiers in Marine Science, 2020)
Eutrophication coupled to climate change disturbs the balance between competition and coexistence in microbial communities including the partitioning of organic and inorganic nutrients between phytoplankton and bacteria. Competition for inorganic nutrients has been regarded as one of the drivers affecting the productivity of the eutrophied coastal Baltic Sea. Yet, it is unknown at the molecular expression level how resources are competed for, by phytoplankton and bacteria, and what impact this competition has on the community composition. Here we use metatranscriptomics and amplicon sequencing and compare known metabolic pathways of both phytoplankton and bacteria co-occurring during a summer bloom in the archipelago of Åland in the Baltic Sea to examine phytoplankton bacteria resource partitioning. The expression of selected pathways of carbon (C), nitrogen (N) and phosphorus (P) metabolism varied over time, independently, for both phytoplankton and bacteria, indicating partitioning of the available organic and inorganic resources. This occurs regardless of eukaryotic plankton growth phase (exponential or stationary) and microbial community composition. Further, the availability of different nutrient resources affected the functional response by the bacteria, observed as minor compositional changes, at class level, in an otherwise taxonomically stable bacterial community. Resource partitioning and functional flexibility seem necessary in order to maintain phytoplankton-bacteria interactions at stable environmental conditions. More detailed knowledge of which organisms utilize certain nutrient species are important for more accurate projections of the fate of coastal waters.